2014
DOI: 10.2528/pier13110703
|View full text |Cite
|
Sign up to set email alerts
|

Setup for Simultaneous Microwave Heating and Real-Time Spectrofluorometric Measurements in Biological Systems

Abstract: Abstract-In this paper, a delivery system allowing simultaneous microwave heating and real-time spectrofluorometric measurements in biological systems is proposed and characterized. This system is used to investigate the phase behavior of lipid bilayers from about 15 • C to 45 • C. The delivery system is based on an open transverse electromagnetic (TEM) cell combined with a spectrofluorometer via an optical cable system. A numerical and experimental dosimetry of the delivery system is conducted. The Specific A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In addition, various studies indicated that the actual molecular mechanism for As 2 O 3 -induced toxicity could be related to its triggering of apoptosis in many cell lines such as the SH-SY5Y cell line [ 18 , 19 ] and brain cells, including primary neurons [ 20 ] and glioma cells [ 21 ]. Finally, in a further effort, we also adapted a transverse electromagnetic cell (TEM cell) [ 22 , 23 , 24 ] onto a digital holographic microscope platform to assess whether CW or GSM-modulated 1800 MHz signals at up to 6 W/kg and steady temperature impacted the well characterized autophagic response of serum-deprived HCT116 cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various studies indicated that the actual molecular mechanism for As 2 O 3 -induced toxicity could be related to its triggering of apoptosis in many cell lines such as the SH-SY5Y cell line [ 18 , 19 ] and brain cells, including primary neurons [ 20 ] and glioma cells [ 21 ]. Finally, in a further effort, we also adapted a transverse electromagnetic cell (TEM cell) [ 22 , 23 , 24 ] onto a digital holographic microscope platform to assess whether CW or GSM-modulated 1800 MHz signals at up to 6 W/kg and steady temperature impacted the well characterized autophagic response of serum-deprived HCT116 cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that small TEM cells have a high useful frequency band. We have previously used the TEM cell shown in Figure 1 as a delivery system for microwaves [8,9,14,27,28] and for nanosecond electric pulses [17,29,30]. The biological sample was placed in a 35-mm Petri dish centered above the TEM cell lower plate.…”
Section: Opened Tem Cellmentioning
confidence: 99%
“…A 12-mm distance between the septum and the lower plate was chosen to allow inserting a Petri dish below the septum of the TEM cell. For this type of TEM cells where the height is rather small compared to the septum width, the E-field has a good uniformity over the TEM cell height [28]. Due to the size of the microscope objective, an aperture with a diameter of 20 mm was made in the center of the lower TEM cell ground plate to allow real-time microscopic observation.…”
Section: Opened Tem Cellmentioning
confidence: 99%